A gap in the recognition of two mycorrhizal factors: new insights into two LysM-type mycorrhizal receptors - He, Junliang; Huang, Renliang; Xie, Xianan (Frontiers in Plant Science, 2024)
Arbuscular mycorrhizal (AM) fungi are crucial components of the plant microbiota, and can form symbioses with 72% of land plants. Researchers have long known that AM symbioses have dramatic effects on plant performance and also provide multiple ecological services in terrestrial environments. The successful establishment of AM symbioses relies on the host plant recognition of the diffusible mycorrhizal (Myc) factors, lipochitooligosaccharides (LCOs) and chitooligosaccharides (COs). Among them, the short-chain COs such as CO4/5 secreted by AM fungi are the major Myc factors in COs. In this review, we summarize current advances, develop the concept of mycorrhizal biceptor complex (double receptor complexes for Myc-LCOs and CO4/5 in the same plant), and provide a perspective on the future development of mycorrhizal receptors. First, we focus on the distinct perception of two Myc factors by different host plant species, highlighting the essential role of Lysin-Motif (LysM)-type mycorrhizal receptors in perceiving them. Second, we propose the underlying molecular mechanisms by which LysM-type mycorrhizal receptors in various plants recognize both the Myc-LCOs and -COs. Finally, we explore future prospects for studies on the biceptor complex (Myc-LCOs and -COs receptors) in dicots to facilitate the utilization of them in cereal crops (particularly in modern cultivated rice). In conclusion, our understanding of the precise perception processes during host plant interacting with AM fungi, where LysM-type mycorrhizal receptors act as recruiters, provides the tools to design biotechnological applications addressing agricultural challenges.